2018
DOI: 10.1016/j.engfracmech.2018.05.036
|View full text |Cite
|
Sign up to set email alerts
|

Meso-scale mixed-mode fracture modelling of reinforced concrete structures subjected to non-uniform corrosion

Abstract: Corrosion-induced concrete cracking is a significant problem affecting the durability of reinforced concrete structures. Considerable research has been carried out in addressing this problem but few have considered the cracking process of concrete as a mixed-mode fracture and the concrete as a multi-phase material. This paper develops a meso-scale mixed-mode fracture model for the cracking of concrete structures under non-uniform corrosion of reinforcement. Concrete is treated as a three-phase heterogeneous ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 43 publications
(32 citation statements)
references
References 47 publications
1
31
0
Order By: Relevance
“…The stage when micro-damage around the rebar forms is difficult to detect experimentally. Nevertheless, the initiation and propagation of the vertical crack are both consistent with the post-mortem experimental observations [81,86,90] and other numerical simulations which utilized the meso-scale structure of concrete [19][20][21]81]. It can be shown by both theoretical and FE analysis that, before fracture occurs, the maximum circumferential stress is located symmetrically about the vertical axis of the rebar [17].…”
Section: Fracture Evolution With the Multiscale Pd Modelsupporting
confidence: 83%
See 1 more Smart Citation
“…The stage when micro-damage around the rebar forms is difficult to detect experimentally. Nevertheless, the initiation and propagation of the vertical crack are both consistent with the post-mortem experimental observations [81,86,90] and other numerical simulations which utilized the meso-scale structure of concrete [19][20][21]81]. It can be shown by both theoretical and FE analysis that, before fracture occurs, the maximum circumferential stress is located symmetrically about the vertical axis of the rebar [17].…”
Section: Fracture Evolution With the Multiscale Pd Modelsupporting
confidence: 83%
“…Meso-scale models have shown their potentials for such problems [18]. However, issues such as the selection of the geometric shape of the aggregates can significantly affect the fracture behavior [19][20][21]. It is possible to use a meso-scale structure acquired from X-ray tomography images [22], but it is computationally costly to extend meso-scale models to meter-scale samples.…”
Section: Introductionmentioning
confidence: 99%
“…Huang et al [10] employed a numerical method to simulate the dynamic fracture of rock under the three-point bending test and found that the crack pattern of the rock beam was changed by the notch location. Xi et al [11][12][13] modelled mesoscale mixed-mode cracking of concrete and found that corrosioninduced concrete cracking is dominated by tensile fracture. Liao et al [14] tried to eliminate the effect of beam gravity in the bending test by applying horizontal forces to the beam and obtained the fracture toughness of rock.…”
Section: Introductionmentioning
confidence: 99%
“…As a kind of homogeneous quasi-brittle material, concrete can be used to make rock-like specimens [12,26]. In order to make jointed rock-like specimens, firstly insert steel piece into the concrete specimen, and take out the steel piece after the initial setting of the concrete specimen.…”
Section: Specimen Preparationmentioning
confidence: 99%
“…Han et al [9] studied the crack growth and rock bridge through mode under different rock bridge lengths, and the inclination through the biaxial cyclic load test. Xi et al [10][11][12] investigated the crack initiation, coalescence, and propagation processes for concrete materials. Then, they quantitatively analyzed the functional relationship between the through strength, the rock bridge dip angle, the friction coefficient of the structural plane, the confining pressure, the connectivity rate and the structural plane dip angle, and proposed the rock bridge through criteria with two non through structural planes.…”
Section: Introductionmentioning
confidence: 99%